2023
DOI: 10.3389/fnins.2023.1049609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex on the APOE4-aging interaction in the white matter microstructure of cognitively normal older adults using diffusion-tensor MRI with orthogonal-tensor decomposition (DT-DOME)

Abstract: The influence of the apolipoprotein E ε4 allele (APOE4) on brain microstructure of cognitively normal older adults remains incompletely understood, in part due to heterogeneity within study populations. In this study, we examined white-matter microstructural integrity in cognitively normal older adults as a function of APOE4 carrier status using conventional diffusion-tensor imaging (DTI) and the novel orthogonal-tensor decomposition (DT-DOME), accounting for the effects of age and sex. Age associations with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Despite the role of APOE in lipid homeostasis, studies do not consistently find an association between APOE -ε4 and worse white matter integrity. 61-63 In previous work, we have shown that the FW measure, particularly in limbic tracts, is sensitive to abnormal aging. 28,49 This study extends this work by showing that APOE -ε4 carriers, who are known to be at greater risk for AD, show these same changes in the FW metric in limbic tracts.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the role of APOE in lipid homeostasis, studies do not consistently find an association between APOE -ε4 and worse white matter integrity. 61-63 In previous work, we have shown that the FW measure, particularly in limbic tracts, is sensitive to abnormal aging. 28,49 This study extends this work by showing that APOE -ε4 carriers, who are known to be at greater risk for AD, show these same changes in the FW metric in limbic tracts.…”
Section: Discussionmentioning
confidence: 96%
“…These morphological and physiological variations within different age and gender groups consequently yield divergent impacts on PI performance, a function involving the entorhinal cortex (Powell et al, 2021)(a Meta-analysis by (Farrer et al, 1997)). Beyond the entorhinal cortex, various other factors such as neurofibrillary tangle (NFT) formation (Ghebremedhin et al, 2001), cerebrospinal fluid (CSF) composition (Altmann et al, 2014), amyloid fibril levels (Cacciaglia et al, 2022), white matter microstructure (Srisaikaew et al, 2023), and functional connectivity within the default mode network (DMN) (Damoiseaux et al, 2012), are similarly influenced by age, gender, and APOE4. Consequently, they could also potentially influence the performance of path integration tasks.…”
Section: Introductionmentioning
confidence: 99%